2007
DOI: 10.1177/03946320070200s202
|View full text |Cite
|
Sign up to set email alerts
|

Forest Bathing Enhances Human Natural Killer Activity and Expression of Anti-Cancer Proteins

Abstract: In order to explore the effect of forest bathing on human immune function, we investigated natural killer (NK) activity; the number of NK cells, and perforin, granzymes and granulysin-expression in peripheral blood lymphocytes (PBL) during a visit to forest fields. Twelve healthy male subjects, age 37-55 years, were selected with informed consent from three large companies in Tokyo, Japan. The subjects experienced a three-day/two-night trip in three different forest fields. On the first day, subjects walked fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
353
2
24

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(423 citation statements)
references
References 22 publications
16
353
2
24
Order By: Relevance
“…These researchers also found that the effect of the forest environments on the NK activity lasted for more than 7 days following the trip, whereas a corresponding trip to an urban area did not cause any changes in NK activity [45]. Based on their most recent study, they report that similar results of increased and lasting NK activity after ''Shinrin-yoku'' were confirmed in female subjects [46].…”
Section: Field Studies On ''Shinrin-yoku''mentioning
confidence: 87%
See 1 more Smart Citation
“…These researchers also found that the effect of the forest environments on the NK activity lasted for more than 7 days following the trip, whereas a corresponding trip to an urban area did not cause any changes in NK activity [45]. Based on their most recent study, they report that similar results of increased and lasting NK activity after ''Shinrin-yoku'' were confirmed in female subjects [46].…”
Section: Field Studies On ''Shinrin-yoku''mentioning
confidence: 87%
“…They first elucidated, by conducting an in vitro experiment, that essential oil(s) or odorous components of wood, such as cypress (hinoki) stem oil, a-pinene, and 1,8-cineole, significantly increased the NK activity, at least partially, via an increase in the intracellular levels of three cytolytic molecules, namely, perforin, granzyme A, and granulysin [43]. They subsequently conducted a field study with healthy male office-workers [44] and found that the NK activity of these office-workers significantly increased after they had experienced a 3-day/ 2-night stay in the forests. This enhancement in NK activity was at least partially mediated by an increase in the expression of the three cytolytic molecules mentioned above.…”
Section: Field Studies On ''Shinrin-yoku''mentioning
confidence: 99%
“…Further, cortisol concentration also holds great significance in terms of human immunological activity. Furthermore, the study of Li et al [34][35][36] reported that forest surroundings could aid in the recovery of the human immune system, as determined from the perspective of NK activity.…”
Section: Experimental Designmentioning
confidence: 99%
“…These repeated conditions may cause the steady stimulation of NK activity. Under similar circumstances, forest bathing trips are reported to enhance NK activity for approximately one month after people visit a forest area and stay for 3 days with a few hours of walking twice a day (41)(42)(43). The surrounding conditions of a forest, particularly near waterfalls, are thought to include plenty of negatively-charged particles.…”
Section: '------Y--j '------Y--jmentioning
confidence: 99%